High-performance non-enzymatic perovskite sensor for hydrogen peroxide and glucose electrochemical detection - He, J.; Sunarso, J.; Zhu, Y.; Zhong, Y.; Miao, J.; Zhou, W.; Shao, Zongping (Elsevier, 2017)
Enzymeless detection of hydrogen peroxide (H2O2) and glucose offers a more reliable and accurate detection route given the absence of enzyme that is sensitive to temperature, pH, poisoning chemicals, and humidity. This can be realized using electrochemical sensor device which at present relies upon platinum, gold, or palladium-based nanostructured electrodes. Finding an alternative to such noble metal materials becomes crucial to facilitate large-scale applications of such device. Here, we reported that La0.6Sr0.4CoO3-d (LSC) perovskite oxide can provide comparable performance to these noble metal nanomaterials. LSC provides superior electrooxidation activities (to H2O2 and glucose) over La0.6Sr0.4Co0.2Fe0.8O3-d (LSCF) and LaNi0.6Co0.4O3 (LNC) that translates to good H2O2 or glucose detection performance. We proposed parallel pathways for H2O2 and glucose oxidations on LSC perovskite, which proceeds via Co3+/Co4+ redox couple and via oxygen vacancies formation. Additionally, reduced graphene oxide (RGO) can be added to optimize the detection performance. The best electrode, i.e., LSC + RGO/GCE provides sensitivity of 500 and 330 µA mM-1 cm-2 for H2O2 and glucose, respectively, and limit of detection of 0.05 and 0.063 µM for H2O2 and glucose, respectively (at S/N = 3). Its respective linear ranges are 0.2–3350 µM and 2–3350 µM for H2O2 and glucose, respectively.